Concrete construction method
Patent Information
- Application Number
- JP2023148021
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-26
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel method for applying concrete. [Background technology]
[0002] In recent years, there has been a demand for shortening construction periods and labor savings in the construction of buildings due to issues such as cost reduction and labor shortages. To shorten construction periods and save labor in construction work, it is important to simplify and streamline work processes. For example, Patent Document 1 describes the development of a system that efficiently plans multiple tasks.
[0003] Meanwhile, concrete hardens one day after being poured, but it takes at least 20 days for it to develop sufficient strength to be used as a structural member. However, in actual construction work, in order to shorten the construction period, it is required to carry out work early after pouring the concrete (before it develops sufficient strength). However, various work carried out during construction can cause defects on the concrete surface. When repairs to such defects are required, this can actually prolong the construction period, so a method of improvement was needed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-90130 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made in consideration of these points, and enables efficient work in construction work that requires cast-in-place concrete. [Means for solving the problem]
[0006] As a result of intensive research into achieving the above-mentioned object, the inventors came up with the idea of a construction method in which a composition containing at least an alkali metal silicate is applied in two separate applications to poured concrete, and completed the present invention.
[0007] That is, the concrete application method of the present invention has the following features. 1. The process of pouring concrete and moist curing it. a first application step of applying a composition (P1) containing at least an alkali metal silicate and an alkylalkoxysilane to the concrete surface after the wet curing is released; a second application step of applying a composition (P2) containing at least an alkali metal silicate after 20 days or more have elapsed since the first application step; A method for constructing concrete comprising the steps of: Effect of the Invention
[0008] According to the concrete construction method of the present invention, various construction work can be carried out soon after pouring the concrete, which is advantageous in shortening the construction period. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described.
[0010] The present invention relates to a method for applying concrete, which is useful in construction work requiring cast-in-place concrete. A process of pouring concrete and moist curing it; a first application step of applying a composition (P1) containing at least an alkali metal silicate and an alkylalkoxysilane to the concrete surface after the wet curing is released; a second application step of applying a composition (P2) containing at least an alkali metal silicate after 20 days or more have elapsed since the first application step; The present invention is characterized by comprising:
[0011] <Concrete curing process> The moist curing method after concrete casting is not particularly limited and can be carried out by a known method. Examples of the moist curing method include - Water-filled curing method in which water is poured onto the surface of concrete; - Water sprinkling curing method, which involves sprinkling water on the surface of concrete; After thoroughly watering the concrete, cover it with a sheet or mat to adhere to the surface of the concrete and prevent water from evaporating. - Wet sand curing, which involves covering the surface of concrete with wet sand to prevent it from drying out; - Spray curing prevents the concrete surface from drying by spraying fine mist of water droplets from a spray nozzle onto the concrete surface, keeping the concrete surface moist. After finishing the concrete surface, a film curing agent is sprayed or applied as soon as possible to prevent water evaporation (water retention curing). etc.
[0012] The moist curing period is determined according to the type of cement and the average daily temperature or the design service life (planned useful life) of the structure. For example, it is the curing period determined in the Standard Specifications for Concrete published by the Japan Society of Civil Engineers or JASS5 by the Architectural Institute of Japan.
[0013] <First coating process> The present invention is characterized in that after the moist curing is released, the first application step involves applying a composition (P1) (hereinafter also referred to as "composition (P1)") containing at least an alkali metal silicate and an alkylalkoxysilane to the surface of the concrete. The first application process in the present invention is a process for primarily increasing the surface strength (hardness) of the poured concrete and suppressing the penetration and adhesion (solidification) of water, dirt, etc. into the concrete. For example, in the construction work of factories, warehouses, etc. (especially large ones), the next construction work is carried out soon after pouring concrete on the floor surface in order to shorten the construction period. In this case, various defects may occur on the concrete surface (floor surface), such as the formation of puddles, contamination by the footprints of workers or tire marks of forklifts, and the formation of cracks. Therefore, it is common to polish and clean the concrete surface when various works are completed. However, if cracks occur due to insufficient strength of the concrete surface, or if water or dirt penetrates and adheres to the inside of the concrete, polishing and cleaning work requires a lot of time and effort. In particular, in cases where the concrete design is used as is (without being painted with color), dirt and other issues can easily become a problem. In response to these problems, the present invention provides a first application step to give the concrete surface a dense structure, temporarily increasing the surface strength (hardness) and suppressing the penetration and adhesion (solidification) of water, dirt, etc. into the concrete. As a result, it is possible to simplify polishing and cleaning work, thereby shortening the construction period. Furthermore, it is possible to maintain the aesthetic design of the concrete.
[0014] The first application step is preferably carried out after the wet curing is released and the concrete surface is in a dry state, specifically, 1 to 10 days after the wet curing is released. After the wet curing is terminated and before the composition (P1) is applied, it is preferable to clean the concrete surface of dust and dirt, if necessary.
[0015] [Composition (P1)] The composition (P1) applied in the first application step of the present invention contains at least (A) an alkali metal silicate and (B) an alkylalkoxysilane. (A) Alkali metal silicate (hereinafter referred to as "Component (A)") is a component that increases the strength of concrete by penetrating into the concrete and reacting with free calcium, magnesium, aluminum, and other polyvalent metal ions in the concrete to produce an insoluble gel that hardens (forming a hardened silicate body).
[0016] As component (A), any water-soluble alkali metal silicate (also called "water glass") represented by the general formula: MO·nSiO (M is at least one alkali metal selected from Li, K, Na, and Cs) can be used. Examples of such component (A) include sodium silicate, sodium orthosilicate, sodium metasilicate, lithium silicate, and potassium silicate. In addition, water glass that is commercially available as an aqueous solution of an alkali metal silicate can also be used. The above alkali metal silicates may be used alone or in a mixture of two or more kinds.
[0017] In the present invention, the component (A) preferably contains at least sodium silicate with a SiO2 / Na2O (molar ratio) of 5 / 1 to 2 / 1 (more preferably 4 / 1 to 3 / 1). Furthermore, in the present invention, it is preferable to use a mixture of potassium silicate having a SiO2 / K2O (molar ratio) of 5 / 1 to 1 / 1 (more preferably 4 / 1 to 1 / 1). In such a case, component (A) can penetrate more easily into the concrete, and the reaction between the silicate and the polyvalent metal ions can be sufficient to form a dense hardened body, which can increase the strength of the concrete surface and also improve its water repellency (the ability to prevent the concrete from absorbing water). As a result, after the first application step, sufficient concrete strength can be ensured for carrying out various construction works, and adhesion and penetration of dirt and the like during the work process can be suppressed.
[0018] The mixing ratio of sodium silicate and potassium silicate, SiO2 / (Na2O+K2O) (molar ratio), is preferably adjusted to 5 / 1 to 1 / 1 (preferably 4 / 1 to 2 / 1), and the SiO2 content is preferably adjusted to 5 to 30 mass% (more preferably 10 to 20 mass%) of the entire composition (P1). Also, the mass ratio of sodium silicate:potassium silicate is preferably 99:1 to 50:50 (more preferably 90:10 to 55:45). When the amount is within this range, excellent water repellency can be exhibited, and uneven application and the like can be suppressed, resulting in a good finish.
[0019] Examples of (B) alkylalkoxysilanes (hereinafter also referred to as "component (B)") include tetrafunctional alkoxysilanes such as tetraethoxysilane, tetramethoxysilane, tetra-n-propoxysilane, tetraisopropoxysilane, tetraisobutoxysilane, tetra-sec-butoxysilane, tetra-t-butoxysilane, and tetraphenoxysilane; trifunctional alkylalkoxysilanes such as methyltrimethoxysilane, methyltriethoxysilane, methyltrippropoxysilane, methyltributoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltrippropoxysilane, ethyltributoxysilane, propyltrimethoxysilane, propyltriethoxysilane, propyltrippropoxysilane, propyltributoxysilane, butyltrimethoxysilane, butyltriethoxysilane, butyltrippropoxysilane, butyltributoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, and phenyltributoxysilane; Bifunctional alkylalkoxysilanes such as dimethyldimethoxysilane, dimethyldiethoxysilane, dimethyldibutoxysilane, diethyldimethoxysilane, diethyldiethoxysilane, diethyldibutoxysilane, diethyldipropoxysilane, dipropyldimethoxysilane, dipropyldiethoxysilane, dibutyldimethoxysilane, dibutyldiethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, diphenyldibutoxysilane, methylphenyldimethoxysilane, and methylphenyldiethoxysilane; and the like. These may be used alone or in combination of two or more.
[0020] In the present invention, it is particularly preferable that the component (B) contains a trifunctional alkylalkoxysilane. Furthermore, it is preferable that the alkyl group has 1 to 3 carbon atoms. Examples of such a component (B) include methyltrimethoxysilane, methyltriethoxysilane, methyltrippropoxysilane, methyltributoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, and propyltriethoxysilane. By containing such a component (B), the permeability of the component (A) into concrete is increased, and the above-mentioned effects can be enhanced.
[0021] The mixing ratio of the component (B) is preferably 0.1 to 15 parts by mass (more preferably 0.5 to 10 parts by mass) per 100 parts by mass of the component (A).
[0022] It is preferable that the composition (P1) of the present invention further contains (C) phosphoric acid or a phosphate (hereinafter also referred to as "component (C)"). Examples of component (C) include phosphoric acid, orthophosphoric acid, ammonium phosphate, ammonium hydrogen phosphate, hydroxyammonium phosphate, and phosphates of alkali metals. In the present invention, it is particularly preferable to contain one or more selected from phosphoric acid, orthophosphoric acid, ammonium phosphate, and ammonium hydrogen phosphate, which can also be used as an aqueous solution.
[0023] The mixing ratio of the component (C) is preferably 0.01 to 15 parts by mass (more preferably 0.03 to 10 parts by mass) per 100 parts by mass of the component (A).
[0024] The composition (P1) of the present invention, which contains the above-mentioned components (A), (B), and (C) in combination, can form a dense hardened body when penetrated into concrete, reduce the water permeability of the concrete, and exhibit excellent effects in sustained water repellency and surface strengthening. Although its mechanism of action is unclear, components (A) and (B) penetrate concrete and react with polyvalent metal ions such as calcium, magnesium, and aluminum released from the concrete to produce an insoluble gel and form a hardened body, and the action of component (C) enhances the hardening properties and allows the formation of a dense hardened body. This reduces the water permeability of the concrete, and as a result, the durability of water repellency and the surface strengthening effect can be improved. In addition, by using the above components (A), (B) and (C) in combination, the oil repellency of concrete can be improved. Due to the above effects, after the first application process, sufficient concrete strength can be ensured to carry out various construction work, and the excellent water and oil repellency can prevent the adhesion and penetration of dirt and the like during the work process.
[0025] Furthermore, by using the above components (A), (B), and (C) in combination, the curability is improved and the elution of unreacted substances from component (A) is suppressed. As a result, the elution of unreacted substances from component (A) due to standing water or running water generated during the work process is suppressed, so there is no risk of the standing water or running water becoming strongly alkaline, and the safety of workers can be ensured.
[0026] The composition (P1) of the present invention is obtained by mixing the above-mentioned components (A), (B), and (C) with water. The amount of water mixed is 10 to 200 parts by mass (preferably 20 to 100 parts by mass) per 100 parts by mass of the above-mentioned component (A). By being in such a range, the composition has excellent permeability into concrete and can fully exhibit the effects of the present invention. The water in the present invention also includes water used as a medium for the components (A) and (C).
[0027] The composition (P1) of the present invention may contain known additives as necessary, so long as they do not significantly impair the effects of the present invention. Examples of such additives include thickeners, film-forming assistants, pH adjusters, leveling agents, wetting agents, plasticizers, antifreeze agents, preservatives, antifungal agents, anti-algae agents, antibacterial agents, deodorants, dispersants, antifoaming agents, adsorbents, flame retardants, coloring pigments, extender pigments, fibers, water repellents, crosslinking agents, ultraviolet absorbers, antioxidants, catalysts, etc.
[0028] Methods for applying the composition (P1) of the present invention include, for example, a method using a coating tool such as a sprayer, coater, roller, or brush, a method of spraying using a known sprayer or watering can, etc., and then spreading it with a mop, etc.
[0029] The amount of the composition (P1) applied depends on the surface condition of the concrete, but is preferably 5 g / m 2 More than 200g / m 2 Less than 10g / m 2 More than 180g / m 2 Less than 15 g / m, more preferably 2 More than 150g / m 2 In such a case, the effect of the present invention can be fully exhibited. After application of the composition (P1), it is preferable to wipe off any excess composition that has not penetrated (impregnated) into the concrete surface and remains on the surface.
[0030] After such a first application step (preferably after 24 hours), various construction work can be carried out.
[0031] <Second coating process> The present invention is characterized in that, 20 days or more (preferably 30 days or more) after the first application step, a composition (P2) (hereinafter also referred to as "composition (P2)") containing at least an alkali metal silicate is applied as a second application step. The second application step in the present invention is a step for increasing the surface strength (hardness) of the poured concrete over the long term and for inhibiting the penetration and adhesion (solidification) of water, dirt, etc. into the concrete.
[0032] In the second application step, before applying the composition (P2), it is preferable to remove and clean the concrete surface (surface layer) from dirt that has adhered (solidified) to the concrete surface (surface layer) due to various construction works and the laitance layer of the surface layer, if necessary.
[0033] [Composition (P2)] The composition (P2) applied in the second application step of the present invention contains at least (A) an alkali metal silicate. As the (A) alkali metal silicate, one selected from the (A) component described in the composition (P1) can be used. In particular, it is preferable that the component (A) contains at least sodium silicate with a SiO2 / Na2O (molar ratio) of 5 / 1 to 2 / 1 (more preferably 4 / 1 to 3 / 1). Furthermore, in the present invention, it is preferable to use a mixture of potassium silicate having a SiO2 / K2O (molar ratio) of 5 / 1 to 1 / 1 (more preferably 4 / 1 to 1 / 1).
[0034] The mixing ratio of sodium silicate and potassium silicate is SiO2 / (Na2O+K2O) (molar ratio) of 5 / 1 to 1 / 1 (preferably 4 / 1 to 2 / 1), and it is preferable to adjust the SiO2 content to 5 to 30 mass% (more preferably 10 to 20 mass%) of the entire composition (P1). When it is in such a range, excellent water repellency can be exhibited, and uneven application and the like are suppressed, resulting in a good finish.
[0035] The composition (P2) of the present invention preferably contains (B) an alkylalkoxysilane and (C) phosphoric acid or a phosphate, similarly to the composition (P1). It may also contain known additives. It is preferable to use the composition (P1) as the composition (P2) of the present invention. This can reduce the water permeability of concrete for a long period of time, thereby improving the durability of water repellency and the surface strengthening effect, and can also improve the oil repellency of concrete.
[0036] Methods for applying the composition (P2) of the present invention include, for example, a method using a coating tool such as a sprayer, coater, roller, or brush, a method of spraying using a known sprayer or watering can, etc., and then spreading it with a mop, etc.
[0037] The amount of the composition (P2) applied depends on the surface condition of the concrete, but is preferably 5 g / m 2 More than 200g / m 2 Less than 10g / m 2 More than 180g / m 2 Less than 15 g / m, more preferably 2 More than 150g / m 2 In such a case, the effect of the present invention can be fully exhibited. After application of the composition (P2), it is preferable to wipe off any excess composition that has not penetrated (impregnated) into the concrete surface and remains on the surface.
[0038] After such a second application step, concrete that has sufficient strength for a long period of time can be obtained by curing the mixture for preferably 24 hours or more. EXAMPLES
[0039] The following examples will clarify the features of the present invention.
[0040] The following raw materials were used: Component (A) (A1) Sodium silicate solution Active ingredients: SiO2 26%, Na2O 7.0% SiO2 / Na2O (molar ratio) = 3.83 (A2) Potassium silicate solution Active ingredients: SiO2 28%, K2O 22.0% SiO2 / K2O (molar ratio) = 1.99 (B) Component (B1) Methyltriethoxysilane (C) Component (C1) Ammonium phosphate aqueous solution (concentration 16.7%, pH=7.0) (C2) Phosphoric acid aqueous solution (concentration 5%, pH=1.0)
[0041] (Composition 1) Composition 1 was obtained by mixing 2 parts by mass of (C1) ammonium phosphate aqueous solution and 100 parts by mass of water, adding and stirring 100 parts by mass of (A1) sodium silicate, and then adding and stirring 4 parts by mass of (B1) methyltriethoxysilane.
[0042] (Composition 2) Composition 2 was obtained by mixing 2 parts by mass of (C1) ammonium phosphate aqueous solution and 100 parts by mass of water, adding and stirring 70 parts by mass of (A1) sodium silicate and 30 parts by mass of (A2) potassium silicate, and then adding and stirring 4 parts by mass of (B1) methyltriethoxysilane.
[0043] (Composition 3) A mixed solution of 4 parts by mass of (B1) methyltriethoxysilane, 3 parts by mass of (C2) phosphoric acid aqueous solution, and 100 parts by mass of water was adjusted to pH 7 using 2-amino-1-propanol. Next, 70 parts by mass of (A1) sodium silicate and 30 parts by mass of (A2) potassium silicate were added and stirred to obtain composition 3.
[0044] Example 1 After pouring and wet curing the concrete, the wet curing was removed and the concrete was dried for 7 days. After cleaning the concrete surface to remove dust, the above composition 1 was applied at a rate of 50 g / m2 as the first application step. 2 It was sprayed with a watering can and spread with a mop. Construction work could begin 24 hours after the first coating process. In addition, 30 days after the first application process, dirt had formed on the concrete surface due to construction work, but it was easily removed. In addition, there were no cracks on the concrete surface, and no dirt had accumulated, so the surface remained in good condition, making it possible to simplify polishing and cleaning work. Next, in the second application step, 50 g / m of the above composition 1 was applied. 2By spreading it with a watering can and then spreading it with a mop, and then drying it (curing for more than 24 hours), we were able to obtain concrete with excellent strength.
[0045] Example 2 After pouring and wet curing the concrete, the wet curing was removed and the concrete was dried for 7 days. After cleaning the concrete surface to remove dust, the above composition 2 was applied at a rate of 50 g / m2 as the first application step. 2 It was sprayed with a watering can and spread with a mop. Construction work could begin 24 hours after the first coating process. In addition, 30 days after the first application process, dirt had formed on the concrete surface due to construction work, but it was easily removed. In addition, there were no cracks on the concrete surface, and no dirt had accumulated, so the surface remained in good condition, making it possible to simplify polishing and cleaning work. Next, in the second application step, the composition 2 was applied at 50 g / m 2 By spreading it with a watering can and then spreading it with a mop, and then drying it (curing for more than 24 hours), we were able to obtain concrete with excellent strength.
[0046] Example 3 After pouring and wet curing the concrete, the wet curing was removed and the concrete was dried for 7 days. After cleaning the concrete surface to remove dust, the above composition 3 was applied at a rate of 50 g / m2 as the first application step. 2 It was sprayed with a watering can and spread with a mop. Construction work could begin 24 hours after the first coating process. In addition, 30 days after the first application process, dirt had formed on the concrete surface due to construction work, but it was easily removed. In addition, there were no cracks on the concrete surface, and no dirt had accumulated, so the surface remained in good condition, making it possible to simplify polishing and cleaning work. Next, in the second application step, the composition 3 was applied at 50 g / m 2 By spreading it with a watering can and then spreading it with a mop, and then drying it (curing for more than 24 hours), we were able to obtain concrete with excellent strength.
Claims
[Claim 1] A process of pouring concrete and moist curing it; a first application step of applying a composition (P1) containing at least an alkali metal silicate and an alkylalkoxysilane to a concrete surface after the wet curing is released; A second application step of applying a composition (P2) containing at least an alkali metal silicate after 20 days or more have elapsed since the first application step; A method for constructing concrete comprising the steps of:
Citation Information
Patent Citations
Process planning system, process planning method, process planning program and computer readable recording medium recording process planning program
JP2003090130A